Functionalization of graphene - Georgakilas, Vasilios (Weinheim an der Bergstrasse, Germany : Wiley-VCH, 2014)
All set to become the standard reference on the topic, this book covers the most important procedures for chemical functionalization, making it an indispensable resource for all chemists, physicists, materials scientists and engineers entering or already working in the field. Expert authors share their knowledge on a wide range of different functional groups, including organic functional groups, hydrogen, halogen, nanoparticles and polymers.
3.5.2 Addition of Chromophores3.5.3 Addition of Polymers; 3.6 Post Functionalization of GO; 3.6.1 Post Functionalization of Organically Modified GO via Click Chemistry; 3.6.2 Counter Anion Exchange; 3.7 Conclusions; References; Chapter 4 Chemical Functionalization of Graphene for Biomedical Applications; 4.1 Introduction; 4.2 Covalent Functionalization of Graphene Nanomaterials; 4.2.1 Synthesis of GO and rGO; 4.2.1.1 Synthesis of Graphene Oxide; 4.2.1.2 Reduction of Graphene Oxide; 4.2.2 Functionalization of Graphene Oxide with Polymers; 4.2.2.1 PEGylated-GO Conjugates.
Includes bibliographical references at the end of each chapters and index.
Online resource; title from PDF title page (ebrary, viewed April 12, 2014).
Keywords: Graphene; Graphene -- Industrial applications; Graphene; Materials; Nanolithography; Nanostructured materials; SCIENCE -- Chemistry -- Inorganic; Graphene; Electronic books